Post Covid Era and Online Payment Systems in India - Chauhan, Saraswati; N P Singh (Industrija, 2024)
Research article presents the online payment systems in India and the impact of Covid on Indian economy, role of financial technologies in facilitating financial transaction for citizens and institutions, and initiatives taken by Reserve Bank of India in the form of creating new digitally embedded organization so that reliance on banking systems is eased and industries (e.g., MSME), entrepreneurs, and citizens can get credit without much of manual paper work. In addition, researchers has also explored the process of the issuance of new licenses to new categories of financial organizations, i.e., establishment of payment banks, trade receivables discounting systems (TReDs), peer-to-peer platforms, regulatory frameworks for account aggregators (AA) and NBFC-AA, establishment of wholly digital loan firms (NBFCs), etc. In addition, the research article analyzed changes in consumer behaviour as a result of the pandemic and digital technology in daily life.